Energy Assessment of Solar Power Plant on-Grid Bi-direction 3 KW 1 Phase - Joewono, Andrew; Angka, Peter R; Sitepu*, Rasional; Yuliati, Yuliati; Antonia, Diana Lestariningsih (Aceh International Journal of Science and Technology, 2023)
The potential for generating electricity from solar energy as one of the renewable energies is suitable for rural areas, small populations, or communal systems. However, this type of power plant requires a high investment budget. Photovoltaic power systems must be designed to meet the demand for electrical energy but require a large supply. To build a more efficient system, it is necessary to build a communal system. For a small population, a 3000-watt power generation system is made. It will be distributed directly to users; a 5000-watt system is made for a larger area. It will be distributed directly to users and interconnected between generators with the principle of load control. In this study, a solar power plant (PLTS) was designed with an on-grid bidirectional system. Solar panels' conversion of electrical energy is channeled to users and stored in a battery backup system. This PLTS system produces a maximum power of 3000 watts by using 8 units of 450wp solar panels, an inverter with a 48-volt on or off-grid mode system, and 4 12V 200 Ah backup batteries. From the measurement results, the PLTS system will start converting DC current into AC with a radiation value of 356 to 1258 W/m2. Produce on-grid AC current energy, a maximum of 2297 watts, and charge backup batteries with DC current, a maximum of 14.3 A. This on-grid (bidirectional) backup PLTS system can convert DC current into AC, supply it directly to the network electricity (grid), and perform energy backups when solar energy is not energized.